Highly reliable wind-rolling triboelectric nanogenerator operating in a wide wind speed range - Yong, Hyungseok (Sci Rep, 2016)
Triboelectric nanogenerators are aspiring energy harvesting methods that generate electricity from the triboelectric effect and electrostatic induction. This study demonstrates the harvesting of wind energy by a wind-rolling triboelectric nanogenerator (WR-TENG). The WR-TENG generates electricity from wind as a lightweight dielectric sphere rotates along the vortex whistle substrate. Increasing the kinetic energy of a dielectric converted from the wind energy is a key factor in fabricating an efficient WR-TENG. Computation fluid dynamics (CFD) analysis is introduced to estimate the precise movements of wind flow and to create a vortex flow by adjusting the parameters of the vortex whistle shape to optimize the design parameters to increase the kinetic energy conversion rate. WR-TENG can be utilized as both a self-powered wind velocity sensor and a wind energy harvester. A single unit of WR-TENG produces open-circuit voltage of 11.2 V and closed-circuit current of 1.86 μA. Additionally, findings reveal that the electrical power is enhanced through multiple electrode patterns in a single device and by increasing the number of dielectric spheres inside WR-TENG. The wind-rolling TENG is a novel approach for a sustainable wind-driven TENG that is sensitive and reliable to wind flows to harvest wasted wind energy in the near future.